Разложить на множители: а(а++1)(b-1)

vyglotov vyglotov    3   10.06.2019 03:50    2

Ответы
veip0 veip0  08.07.2020 17:25
A(a+2) - (b+1)(b-1) = a² + 2a - b² + b - b + 1  = a² + 2a - b² + 1(a² + 2a + 1) - b² = (a+1)² - b² = (a+1-b)(a+1+b)
квадрат первого                               разница            
числа + удвоенное                         квадратов
произведение первого
на второе минус квадрат
второго числа
ПОКАЗАТЬ ОТВЕТЫ
A(a+2)-(b+1)(b-1)=a²+2a-b²+1=(a²+2a+1)-b²=(a+1)²-b²=(a+1-b)(a+1+b)
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра